PENYALAHGUNAAN KEWENANGAN PEJABAT PUBLIK DALAM PENANGGULANGAN JUDI ONLINE SEBAGAI SUAP TINDAK PIDANA KORUPSI - Aini, Nur; Farafishah, Nailah; Rizkiah, Nurfatiha (Legislatif, 2025)
The abuse of authority by public officials in addressing online gambling reveals weaknesses in the integrity and accountability system of state apparatus. The Ministry of Communication and Digital Affairs (Komdigi), which is normatively authorized to block gambling websites, was instead involved in practices protecting illegal sites in exchange for certain benefits. This study aims to analyze the forms of such abuse of authority and to demonstrate that the conduct of public officials in this case fulfills the elements of bribery in office as regulated under the Anti-Corruption Law, which are not reflected in the application of the Electronic Information and Transactions Law. This research employs normative legal research using a statutory approach to comprehensively examine the provisions of Article 12 letter (a), as well as a conceptual approach to assess the qualification of receiving gifts or promises due to official position as an offense of office under corruption law. The findings indicate that the actions of public officials who allowed certain online gambling sites to continue operating while receiving financial benefits satisfy the elements of Article 12 letter (a) of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption. The conclusion emphasizes that the conduct of Komdigi officials should not be regarded as a technical violation of the EIT Law, but rather as a corruption offense characterized by abuse of authority based on official position, thereby placing it within the corruption law regime as the basis for public officials’ criminal liability.